2018
DOI: 10.1371/journal.pone.0201840
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and functional parameters: A cross-sectional study in an older population

Abstract: The present study aims to clarify the association of vitamin D status with functionality, measured through gait speed and hand grip strength, in a sample of older adults, considering sex-specific characteristics and the potential confounding effect of lifestyle factors, disease, skin phenotype, season of blood collection and vitamin D supplementation. The Nutrition UP 65 cross-sectional study was conducted in a population-based sample of 1,425 older adults ≥ 65 years old. Serum levels of 25-hydroxyvitamin D we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 66 publications
1
15
1
2
Order By: Relevance
“…Previous studies have revealed controversial results regarding the relationship between vitamin D and hand grip strength [4,47,48]. Our results could contribute to clarify the association between vitamin D and hand grip strength, providing more complete information about bone metabolism biomarkers in an older population which was not considered in other studies [4,42,43,44]. In addition, our results were adjusted for a set of covariables, such as age and gender.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies have revealed controversial results regarding the relationship between vitamin D and hand grip strength [4,47,48]. Our results could contribute to clarify the association between vitamin D and hand grip strength, providing more complete information about bone metabolism biomarkers in an older population which was not considered in other studies [4,42,43,44]. In addition, our results were adjusted for a set of covariables, such as age and gender.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, more extraskeletal effects of vitamin D have been revealed, and the diverse functions of vitamin D have also been supported by the discovery that vitamin D receptors (VDRs) and vitamin D activating enzymes (hydroxylases) are present in the tissues and cells not involved in mineral and bone metabolism. Because VDRs have been located in multiple tissues, vitamin D deficiency has been associated with an increased risk of chronic diseases such as cardiovascular disease, diabetes, and dementia [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we did not consider the impact of vitamin D on the quality of life, functional status and neither on the metabolic parameters, that have been previously related with vitamin D levels and with long-term outcomes [45,46] In fact, in our study patients with lower vitamin D displayed higher glycemia and cholesterol levels, even despite a larger use of statins.…”
Section: Limitationsmentioning
confidence: 79%
“…In 2018, Mendes et al evaluated 1,425 older people individuals (mean age: 75.4 ± 7.5 years in women and 74.2 ± 6.7 years in men) and found a signi cant association between vitamin D de ciency and decreased gait speed and HGS, especially in men (41.5% of the total sample) [22]. Of the participants of our study, only 28% were men, with a much smaller age group (67.18 ± 5.33 years), which could explain, at least in part, the con icting results.…”
Section: Discussionmentioning
confidence: 99%